Bionic liquid crystal composition, application and cosmetic
By using a composite emulsifier and bionic lipo component in liquid crystal products, a bionic liquid crystal composition with high liquid crystal strength and delicate structure is formed, which solves the problem of insufficient number and strength of liquid crystals in existing liquid crystal products, and significantly improves the repair effect.
Patent Information
- Application Number
- CN202411898702.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
Existing liquid crystal products rarely load bionic fat, resulting in insufficient liquid crystal quantity and liquid crystal strength, which in turn affects the repair effect.
The preferred composite emulsifier and the bionic lesion component are combined to form a delicate liquid crystal structure and a bionic liquid crystal composition with high liquid crystal strength.
The number of liquid crystals and liquid crystal strength of the liquid crystal material are improved, and the repair effect of the liquid crystal material is significantly improved.
Smart Images

Figure CN119679659A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of daily chemicals, and in particular to a bionic liquid crystal composition, application and cosmetics. Background Art
[0002] Liquid crystal skin care products, with their unique liquid crystal phase structure, have brought revolutionary innovation to the field of skin care. Compared with traditional skin care products, liquid crystal systems show significant advantages based on skin science and materials science. They can not only simulate the layered structure of the skin's stratum corneum and provide a more excellent moisturizing effect, but also enhance the skin's ability to absorb nutrients by optimizing the sustained release system of active ingredients. In addition, liquid crystal skin care products have excellent performance in stability, reducing skin irritation, and improving the user experience. These characteristics make them highly regarded in skin care products and become an important direction for cosmetic scientific research and market development. With the growing demand of consumers for efficient and safe skin care products, the application prospects of liquid crystal technology are broad, and its scientificity and practicality are gradually being recognized by academia and industry. Emulsifiers that can form liquid crystals in the market include sucrose esters, glucosides, lecithins, olive esters, phosphates, stearoyls, etc.
[0003] For relevant solutions for LCD products, please refer to the following documents:
[0004] Publication No. CN103565662B, the subject is a water-resistant liquid crystal cosmetic, which discloses the use of a compound emulsifier to prepare a water-resistant liquid crystal material, the compound emulsifier being: behenyl alcohol, polyglyceryl-10 pentastearate, sodium stearoyl lactylate;
[0005] Publication No. CN114617778A, the subject is a natural liquid crystal structure composition, a preparation method and application thereof, which discloses the use of a compound emulsifier to prepare a natural liquid crystal structure, and the compound emulsifier is: polyglycerol-10 pentastearate, glyceryl monooleate and sodium stearoyl glutamate.
[0006] There are few solutions for loading bionic fetal fat in existing liquid crystal products. The solutions that have been made public can be seen in the following records:
[0007] Publication No. CN117122533B, the subject is a bionic vernix caseosa composition and its preparation method and application, which discloses the use of polyglycerol-6 distearate and palmityl alcohol as liquid crystal emulsifiers, loaded with bionic vernix caseosa composed of phytosterols, hydrogenated lecithin and ceramide NP;
[0008] The function of this solution is to slow down the rate of water loss from the skin and achieve a continuous moisturizing effect.
[0009] After research, it was found that the components of bionic vernix caseosa will participate in the formation of liquid crystal structure, which will affect the number and strength of liquid crystals; similarly, the liquid crystal structure will also affect the repair effect of bionic vernix caseosa.
[0010] Therefore, the technical problem solved by the present invention is: how to increase the amount and strength of liquid crystals in the liquid crystal material having a bionic fetal fat component, and how to further improve the repairing effect of the liquid crystal material. Summary of the invention
[0011] The purpose of the present invention is to provide a bionic liquid crystal composition, which is formulated with a preferred composite emulsifier and a bionic fetal fat component to obtain a liquid crystal composition with fine liquid crystal morphology, high liquid crystal strength and good repair effect.
[0012] Meanwhile, the invention also discloses an application of the composition and cosmetics.
[0013] To achieve the above objectives, this application discloses:
[0014] A bionic liquid crystal composition, comprising an emulsifier for forming a liquid crystal structure and a bionic composition;
[0015] The emulsifier is composed of behenyl alcohol, polyglyceryl-10 pentastearate, and sodium stearoyl glutamate; the weight ratio of the behenyl alcohol, polyglyceryl-10 pentastearate, and sodium stearoyl glutamate is 30-45:35-55:6-10;
[0016] The biomimetic composition includes hydrogenated lecithin, sterol, and ceramide NP;
[0017] The weight ratio of the behenyl alcohol to the bionic composition is 30-45:8.9-15.1.
[0018] The present invention uses behenyl alcohol, polyglyceryl-10 pentastearate, and sodium stearoyl glutamate alone to form liquid crystals, and verifies that they can form a relatively fine liquid crystal structure with strong liquid crystal stability; after the bionic composition is added to the above-mentioned emulsifier, the fineness of the liquid crystal and the liquid crystal strength are not weakened, indicating that the formula of the present invention is a liquid crystal material that can effectively load the bionic composition.
[0019] At the same time, the present invention also verifies other compound emulsifiers that can form similar liquid crystal structures. When the bionic composition is added to other compound emulsifiers, the liquid crystal fineness and liquid crystal strength thereof are weakened to varying degrees. Through the experiments of the present invention, it can be proved that regardless of whether the bionic composition participates in the formation of the liquid crystal structure or constitutes one of the components of the liquid crystal structure, it will have an impact on the liquid crystal structure.
[0020] In addition, the present invention also verifies the influence of different liquid crystal structures on the skin repair performance of the bionic composition. When the liquid crystal structure is finer and the strength is greater, the skin repair performance of the bionic composition with the same dosage is better.
[0021] In the above-mentioned biomimetic liquid crystal composition, the weight ratio of the hydrogenated lecithin, sterol and ceramide NP is 8-13:0.8-2:0.1.
[0022] In the above-mentioned biomimetic liquid crystal composition, the sterol is a plant sterol substance;
[0023] The phytosterols are one or more combinations of β-sitosterol, campesterol and lysosterol.
[0024] In the above-mentioned bionic liquid crystal composition, the weight ratio of the behenyl alcohol, polyglycerol-10 pentastearate, and sodium stearoyl glutamate is 40-45:35-40:7-10; the weight ratio of the hydrogenated lecithin, sterol, and ceramide NP is 9-12:0.8:0.1.
[0025] The bionic liquid crystal composition further comprises tocopherol acetate, and the weight ratio of behenyl alcohol to tocopherol acetate is 40-45:0.05-0.2.
[0026] At the same time, the present invention also discloses the use of any of the above-mentioned bionic liquid crystal compositions in preparing cosmetics.
[0027] Finally, the present invention also discloses a cosmetic comprising any of the above-mentioned bionic liquid crystal compositions.
[0028] The above-mentioned cosmetic contains 1-5wt% of the bionic liquid crystal composition.
[0029] This application has at least the following beneficial effects:
[0030] The composition of the present invention is formulated with a preferred composite emulsifier and a bionic fetal fat component to obtain a liquid crystal composition with fine liquid crystal morphology, high liquid crystal strength and good repair effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a microscope photo of the liquid crystal of sample 1;
[0032] Figure 2 This is a microscope photo of the liquid crystal of sample 2;
[0033] Figure 3 This is a microscope photo of the liquid crystal of sample 3;
[0034] Figure 4 This is a microscope photo of the liquid crystal of sample 3;
[0035] Figure 5 This is a microscope photo of the liquid crystal of sample 5;
[0036] Figure 6 This is a microscope photo of the liquid crystal of sample 6;
[0037] Figure 7 This is a microscope photo of the liquid crystal of sample 7;
[0038] Figure 8 This is a microscope photo of the liquid crystal of sample 8;
[0039] Fig. 9 This is a microscope photo of the liquid crystal of sample 9;
[0040] Fig.10 is a microscope photograph of the liquid crystal of sample 10;
[0041] Figures 1 to 10 The scale bar length in is 100 μm. DETAILED DESCRIPTION
[0042] Below in conjunction with embodiments of the present invention, the present invention is clearly and completely described. In the description of the present invention, it should be noted that, in the embodiments, those not indicating specific conditions, are carried out according to the conditions of normal conditions or manufacturer's suggestions. Reagents used or instruments not indicating manufacturers are conventional products that can be obtained by commercial purchase. In the case of not making special instructions, the parts used in the embodiments of the present invention are all parts by weight.
[0043] Examples and Comparative Examples
[0044] A method for preparing a bionic liquid crystal composition comprises the following steps: mixing the components described in Table 1 under stirring conditions, heating to 70-80° C., mixing evenly, cooling, and granulating to obtain the bionic liquid crystal composition.
[0045] The relevant formula can be found in Table 1;
[0046] Table 1 Formula Unit: g
[0047]
[0048] The phytosterols were purchased from Haisifu; the active ingredient was β-sitosterol; the content of the active ingredient was ≥30wt%.
[0049] Application formula of liquid crystal emulsion
[0050] The application formula of the liquid crystal emulsion is shown in Table 2 below;
[0051] The preparation method of the application formula is:
[0052] Step 1: After the raw materials EMT 15 and carbomer of phase A are dispersed evenly, glycerol, disodium EDTA and 1,2-hexanediol are added, mixed evenly, heated to 80-85°C, p-hydroxyacetophenone and biomimetic liquid crystal composition are added, stirred evenly until there is no obvious insoluble matter, and set aside;
[0053] Step 2: Add phase B coconut oil alcohol-caprylic acid / capric acid ester, polydimethylsiloxane, and cetearyl alcohol to the oil phase in sequence, mix well, heat to 80-85°C, and set aside;
[0054] Step 3: Before emulsification, add coenzyme Q10 to the oil phase and stir evenly. Turn on the stirring, add the oil phase raw materials to the water phase, homogenize for 3-5 minutes, and then start cooling.
[0055] Step 4: Cool down to 38℃, and discharge after passing the inspection;
[0056] Table 2 Application formula
[0057] Mutually Components Recipe 1 Recipe 2 Recipe 3 A water To 100 To 100 To 100 A EMT 15 0.15 0.15 0.15 A Carbomer 0.2 0.2 0.2 A Disodium EDTA 0.02 0.02 0.02 A glycerin 10 5 15 A p-Hydroxyacetophenone 0.2 0.2 0.2 A 1,2-Hexanediol 1 1 1 A Bionic liquid crystal composites 3 1 5 B Cetearyl Alcohol 3 2 4 B Coco-Caprylate / Caprate 10 8 12 B Dimethicone 2 2 2 B Coenzyme Q10 0.1 0.1 0.1
[0058] The chemical name of EMT 15 is: Hydroxyethyl acrylate / sodium propylene dimethyl taurate copolymer.
[0059] Performance Test 1
[0060] The bionic liquid crystal composition prepared in Example 5 was applied to Formula 1 to Formula 3 to obtain Samples 1 to 3, and the following tests were performed:
[0061] 1. Stability test;
[0062] 2. Microscope observation of liquid crystal structure;
[0063] 3. Moisturizing test;
[0064] 4. Active ingredient transdermal absorption test.
[0065] Among them, the test method of stability test is:
[0066] Heat resistance test: Put the sample into a 45℃ constant temperature box for 30 days, take it out, return it to room temperature and observe whether there is oil-water separation, observe whether the consistency changes to judge the heat resistance of the sample, and observe whether the liquid crystal strength is significantly weakened or disappears; if any of the above situations occurs, it will be judged as unqualified.
[0067] Cold resistance test: Put the sample into a -18℃ constant temperature box for 30 days, take it out, restore it to room temperature and observe whether there is oil-water separation, observe whether the consistency changes to judge the heat resistance of the sample, and observe whether the liquid crystal strength is significantly weakened or disappears; if any of the above situations occurs, it will be judged as unqualified.
[0068] The test method for liquid crystal strength is:
[0069] A polarizing microscope (DM750, Leica) was used to observe the morphology, particle size and uniformity of the prepared liquid crystal composition under the polarized field of view after magnification 100 times, and a camera was used to collect image data. The particle size, uniformity and liquid crystal structure of each sample under the microscope were compared, and a comprehensive score (0-10 points) was given.
[0070] Moisturizing test - skin moisture content test:
[0071] The moisture content (MMV) of the stratum corneum of the skin can directly reflect the dryness of the skin, and thus reflect the moisturizing effect of the product. The moisture content of the stratum corneum of the test site is measured using the Skin-sp skin tester skin moisture test probe, and the average of 5 measurements is taken as the test value, and the result is expressed in MMV. The MMV values of the cheeks of the subjects before and after using the sample at different times are measured, and the MMV change rate of the sample is calculated by the following formula to evaluate the moisturizing performance of the compound moisturizer.
[0072]
[0073] The test method for the transdermal absorption rate of active ingredients is the Franz diffusion cell method:
[0074] Experimental principle: Install the ex vivo skin of human or animal on the diffusion cell, take the receiving liquid at regular intervals, determine the content of active ingredients with appropriate analytical methods, and calculate the cumulative penetration per unit area to evaluate the permeability of chemicals.
[0075] Specific method: Take a piece of intact pig skin, clean the fine hair on its surface with tweezers, and remove the subcutaneous fat with a scalpel; then wash it with phosphate buffered saline (PBS), wrap it with tin foil and place it in a -20℃ refrigerator for later use. Thaw the treated skin in PBS with pH=6.5 for 30 minutes, wash the pig skin with deionized water and cut it into about 4cm 2 The pig skin was placed in a diffusion cell with the epidermal side facing the dosing chamber. The surface area of the diffusion cell was 1.33 cm 2 At the same time, add 15 mL of normal saline into the receiving chamber as the receiving liquid (mark the liquid level of the sampling tube to ensure that the liquid level is consistent after sampling and resampling). During the addition process, ensure that the bubbles are discharged and add a magnetic stirrer (keep the size of the stirrer basically consistent).
[0076] Add 1 mL of the sample to be tested into the supply cell, then place the Franz diffusion cell into the transdermal diffusion tester, set the experimental temperature to 32±1°C, seal the supply cell port with plastic wrap, and set the stirring speed to 500r / min. Use a sampling needle to take 1 mL of samples at the beginning of the experiment at 1, 2, 3, and 4 hours, respectively, and add an equal volume of isothermal saline. After microporous filtration of the samples, HPLC is used to analyze the coenzyme Q10 content therein.
[0077] After the reaction, the pig skin was taken out, and the residual sample on the surface of the pig skin was removed with absorbent cotton. The skin was cut into pieces and collected in a centrifuge tube. 2 mL of normal saline was added and ultrasonicated for 30 min. A refrigerated centrifuge was used to centrifuge at 5000 r / min for 10 min. The supernatant was taken, filtered through a microporous filter, and the coenzyme Q10 content was analyzed by HPLC. Cumulative permeation per unit area (μg·cm -2 ) is calculated according to the following formula:
[0078]
[0079] Where:
[0080] Q n —Cumulative transdermal volume per unit area;
[0081] V—total volume of receiving solution (mL); 15ml
[0082] V i —The volume of liquid taken each time (mL); 1ml
[0083] C n — is the drug concentration in the receiving pool at the nth time point;
[0084] C i — is the drug concentration in the receiving pool at the i-th time point
[0085] The effective diffusion area in the experiment is A = 1.33 cm -2
[0086] Test result reference Figures 1 to 3 , and Table 3;
[0087] Table 3 Test results
[0088]
[0089] Result analysis:
[0090] It can be seen from the test results in Table 3 that after Example 5 of the present invention is applied to application formulas 1 to 3, it can show stability under cold and hot conditions, has a large liquid crystal strength, a good moisture retention rate, and can effectively promote the penetration and absorption of active ingredients. By comparing the data in Table 3 with the data in Table 4, it can be found that the use of a small amount of tocopherol acetate can slightly improve the skin's moisture content and the penetration of active ingredients; we believe that tocopherol acetate is an antioxidant that can improve the skin's antioxidant and free radical scavenging properties, and has a positive effect on the performance of the sebum biomimetic composition on the skin surface, thereby improving the skin's moisture content.
[0091] Performance Test 2
[0092] Based on Formula 1, the functions of the bionic liquid crystal compositions of the embodiments and comparative examples were verified, and the test items were the same as those of Performance Test 1;
[0093] The sample numbers corresponding to Examples 1 to 4 are Sample 4 to Sample 7;
[0094] The sample numbers corresponding to Comparative Examples 1 to 3 are Sample 8 to Sample 10.
[0095] Test result reference Figures 4 to 10 , and Table 4;
[0096] Table 4 Test results
[0097]
[0098] Result analysis:
[0099] Through the testing of samples 4 to 7 of the present invention, it can be seen that the samples of the present invention can maintain good stability at high and low temperatures, have high liquid crystal strength, and have good water retention and penetration-promoting effects.
[0100] By comparing sample 7 and sample 10 of the present invention, it can be seen that in the absence of plant sterols and ceramide NP, the liquid crystal stability, strength and storage stability have changed, which confirms the conclusion of the present invention that the bionic composition may be involved in the formation of liquid crystals. Among them, the liquid crystal strength of sample 10 is 10, indicating that the emulsifier of the present invention has very good liquid crystal strength. The emulsifier shows a significant weakening of the liquid crystal under high temperature conditions; in sample 7 of the present invention, this liquid crystal weakening phenomenon disappears. At the same time, since sample 10 does not contain a bionic composition, its moisturizing ability and penetration effect are also significantly reduced. Generally speaking, bionic sebum itself does not have an obvious penetration-enhancing effect, so it can be roughly known that the penetration efficiency of the application formula of the present invention combined with the liquid crystal emulsifier is 0.582μg·cm -2When the bionic composition is used in combination with the liquid crystal emulsifier, the penetration efficiency is significantly increased and the moisturizing performance is also significantly enhanced.
[0101] It can be seen from Samples 7, 8 and 9 of the present invention that the simultaneous use of sodium stearoyl glutamate and behenyl alcohol can improve the liquid crystal stability and strength to a certain extent, wherein the liquid crystal structure in which behenyl alcohol participates can significantly promote the penetration of active ingredients, and for liquid crystal strength and liquid crystal stability, the importance of behenyl alcohol is significantly greater than that of sodium stearoyl glutamate.
[0102] It can be seen from the above cases that liquid crystal emulsifiers are still the main ingredients for achieving enhanced penetration, and liquid crystal emulsifiers and bionic compositions are the main ingredients for achieving better moisturizing effects. The selection of appropriate liquid crystal emulsifiers and the use of bionic compositions can significantly improve the moisturizing and penetration properties.
[0103] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that the equivalents falling within the claims be included. All changes in the meaning and scope of the elements are encompassed by the present invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A biomimetic liquid crystal composition, characterized in that: It includes an emulsifier and a biomimetic composition for forming a liquid crystal structure; The emulsifier is composed of behenyl alcohol, polyglyceryl-10 pentastearate, and sodium stearoyl glutamate; the weight ratio of the behenyl alcohol, polyglyceryl-10 pentastearate, and sodium stearoyl glutamate is 30-45:35-55:6-10; The biomimetic composition includes hydrogenated lecithin, sterol, and ceramide NP; The weight ratio of the behenyl alcohol to the bionic composition is 30-45:8.9-15.
1.
2. The biomimetic liquid crystal composition according to claim 1, characterized in that: The weight ratio of the hydrogenated lecithin, sterol and ceramide NP is 8-13:0.8-2:0.
1.
3. The biomimetic liquid crystal composition according to claim 2, characterized in that: The sterol is a plant sterol substance; The phytosterols are one or more combinations of β-sitosterol, campesterol and lysosterol.
4. The biomimetic liquid crystal composition according to claim 1, characterized in that: The weight ratio of the behenyl alcohol, polyglyceryl-10 pentastearate and sodium stearoyl glutamate is 40-45:35-40:7-10; The weight ratio of the hydrogenated lecithin, sterol and ceramide NP is 9-12:0.8:0.
1.
5. The biomimetic liquid crystal composition according to claim 1, characterized in that: It also includes tocopherol acetate, and the weight ratio of behenyl alcohol to tocopherol acetate is 40-45:0.05-0.
2.
6. Use of the bionic liquid crystal composition according to any one of claims 1 to 5 in preparing cosmetics.
7. A cosmetic, characterized in that: A bionic liquid crystal composition comprising any one of claims 1 to 5.
8. The cosmetic according to claim 7, characterized in that: Contains 1-5wt% of the bionic liquid crystal composition.
Citation Information
Patent Citations
A water-resistant liquid crystal cosmetic
CN103565662B
A bionic fetal fat composition and its preparation method and application
CN117122533B
Natural liquid crystal structure composition as well as preparation method and application thereof
CN114617778A
Anti-wrinkle and anti-aging composition as well as preparation method and application thereof
CN115778870A
Bionic tire fat composition as well as preparation method and application thereof
CN117122533A